Those Without Sin: Voices of Color on White Protestant Christianity in Nineteenth-Century American Literature - Redmond, Charles. (2017)
Abstract: This dissertation illustrates how whiteness as property, reified by unjust laws and domestic policies in the United States in the nineteenth century, corrupts Protestant Christianity as practiced by white people. Through an analysis of the writings of William Apess, William Wells Brown, Harriet E. Wilson, John Rollin Ridge, María Amparo Ruiz de Burton, and ZitkalaŠa, I show that writers of color were unafraid to criticize openly the rampant racism masquerading as religion. Through both their fiction and non-fiction, these authors, when read together, critique whiteness and its pernicious effect on all of American society, demonstrating that Christian charity and democratic civilization are incompatible with principles that elevate one race of people over all others. Drawing upon a range of disciplines, including theology, critical race studies, and legal theory, I situate the texts I discuss as part of a discourse that creates a portrait of the white race as a people incapable of reconciling their race prejudice with the rhetoric of Christian virtue and the U.S. Constitution's promise of life, liberty, and the pursuit of happiness. Apess, Brown, Wilson, Ridge, Ruiz de Burton, and Zitkala-Ša all call upon their white counterparts to live up to their professed ideals of democracy or give up the fantasy of American Exceptionalism. Most importantly, all of them draw attention to the unresolved question of which version of Christianity people should follow and what role it will play in shaping the nation. Arguing that these authors of color recognized whiteness as property as an evil antithetical to Christianity, as well as to the U.S. Constitution, my first chapter focuses on Apess's works (1833-1836) as an early attack on whiteness—specifically, skin color—being used to determine church membership and citizenship. I then read Wilson's Our Nig (1859) and Brown's Clotel (1853) in Chapter Two as examples of what Veronica T. Watson calls "the literature of white estrangement," with each author detailing how Christian charity comes second only to whiteness in white American hearts. Chapter Three discusses Ridge's The Life and Adventures of Joaquin Murieta (1854) and Ruiz de Burton's Who Would Have Thought It? (1872) as continuations of the critique of whiteness, with each author critiquing Protestant Christianity's role in the imperialist designs of the U.S. by focusing on its investment in whiteness as property. My final chapter analyzes Zitkala-Ša's American Indian Stories (1921) as a wholesale rejection of a white-led Indian reform project that, despite its purportedly charitable Christian intentions, was in reality intended to deny Native Americans the rights and economic privileges of full citizenship. Politically, persons of color were virtually non-existent in the original composition of the U.S. Constitution and consequently lacked any political means to challenge the social contract that governed them. White men championed and fought for revolution, white men championed and pushed for nullification of federal laws, and white men championed and initiated secession. Denied a political voice, some of those who were not white males used literature to affect the world around them. Recognizing this fact, my dissertation explores the links that exist among authors typically relegated to a status outside both the right to citizenship and the traditional canon. In grouping these authors, I am reminded of Winston Churchill's oft-quoted bon mot: "History is written by the victors." But instead of despairing at this commonplace, I listen to voices of dissent, especially those of writers of color who point out the blatant hypocrisy of white Christians in the nineteenth century. Ultimately, the texts I discuss prove that resistance to whiteness is perhaps the oldest form of political activism in the United States; Thesis (Ph.D.)--Tufts University, 2017.; Submitted to the Dept. of English.; Advisor: Elizabeth Ammons.; Committee: Nate Wolff, Modhumita Roy, and Elizabeth Fenton.; Keywords: American literature, and Religion.